O Projeto de Integração do Rio São Francisco (PISF): uma estratégia piloto de Inteligência Territorial para o PSH - Lucas Costa Rodrigues; Aldo Aloísio Dantas (Confins)
This article investigates the application of the São Francisco River Integration Project (PISF) as a pilot strategy within the Water Safety Panel (PSH), highlighting its significant role in planning and decisions related to public policies of water safety in Brazil. The PISF serves as an analysis laboratory for challenges associated with Brazilian water safety, generating valuable insights and emphasizing the importance of territorial intelligence in implementing effective solutions. The analysis focused on the PISF exemplifies how an approach that integrates territorial and technological reflections can offer a deep understanding of current water challenges, stimulating future collaborations and strategic advancements in water safety.